"It's Just Not the Whole Story": Black Perspectives of Protest Portrayals. Issue 4 (8th August 2022) - Brown, Danielle K.; Wilner, Tamar; Masullo, Gina M.
Abstract: News organizations have a long history of covering civil rights protests in delegitimizing ways, and scholars have found that this coverage negatively affects public opinion. However, most media effects work has minimized the perspectives of Black people, and little is known about how racial identity might affect how protest coverage is perceived. We both survey ( n = 1, 052) and interview ( n = 27) Black Americans to provide a rich understanding and interpretation of how they see and experience media coverage and how that influences them. We contribute to the literature by showing that Black Americans are dissatisfied with how news media cover their communities and covers protests, and they feel this coverage reifies harmful stereotypes and perpetuates invisibility politics.